2004
DOI: 10.1152/ajplung.00280.2003
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid inhibition ofSP-Agene expression in lung type II cells is mediated via the TTF-1-binding element

Abstract: In lung cells transfected with a fusion gene containing three TBEs fused to the basal SP-A promoter, Dex prevented the stimulatory effect of IL-1 on TTF-1 induction of SP-A promoter activity, suggesting that the GR inhibits SP-A promoter activity through the TBE. In gel shift assays using nuclear extracts from human fetal type II cells cultured in the absence or presence of cAMP, Dex markedly reduced binding of nuclear proteins to the TBE and blocked the stimulatory effect of cAMP on TBE-binding activity. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Previously, we observed that 378 bp of 5Ј-flanking DNA from the rabbit SP-A gene were sufficient to direct appropriate lung cell-specific and developmental regulation of expression in transgenic mice (4). In human fetal type II cell transfection studies using reporter constructs containing 5Ј-flanking sequences from the hSP-A2 gene, we observed that the TBE at Ϫ171 to Ϫ166 bp plays a critical role in cAMP, IL-1, and glucocorticoid regulation of hSP-A2 promoter activity (5,25,27,38). In the present study, we created transgenic mouse lines carrying hSP-A:hGH fusion genes comprised of 313 bp of hSP-A2 5Ј-flanking DNA, without and with a scramble mutation in the TBE (hSP-A Ϫ313TBEmut :hGH) and a fusion gene comprised of 175 bp of 5Ј-flanking sequence containing the core TBE, E-box, and G/T-box sequences, but lacking the ERRE.…”
Section: Hsp-a2 (175 Bp) 5ј-flanking Dna Is Sufficient For Lung Cell-mentioning
confidence: 79%
See 1 more Smart Citation
“…Previously, we observed that 378 bp of 5Ј-flanking DNA from the rabbit SP-A gene were sufficient to direct appropriate lung cell-specific and developmental regulation of expression in transgenic mice (4). In human fetal type II cell transfection studies using reporter constructs containing 5Ј-flanking sequences from the hSP-A2 gene, we observed that the TBE at Ϫ171 to Ϫ166 bp plays a critical role in cAMP, IL-1, and glucocorticoid regulation of hSP-A2 promoter activity (5,25,27,38). In the present study, we created transgenic mouse lines carrying hSP-A:hGH fusion genes comprised of 313 bp of hSP-A2 5Ј-flanking DNA, without and with a scramble mutation in the TBE (hSP-A Ϫ313TBEmut :hGH) and a fusion gene comprised of 175 bp of 5Ј-flanking sequence containing the core TBE, E-box, and G/T-box sequences, but lacking the ERRE.…”
Section: Hsp-a2 (175 Bp) 5ј-flanking Dna Is Sufficient For Lung Cell-mentioning
confidence: 79%
“…SP-A expression in cultured human fetal lung explants and isolated type II cells is stimulated by hormones and factors that increase cAMP (2,51) and by interleukin-1 (IL-1) (25) and is inhibited by glucocorticoids, such as dexamethasone (Dex) (5,50,52). cAMP and IL-1 stimulation of SP-A expression is O 2 dependent (1,25,26).…”
mentioning
confidence: 99%
“…Expression of several genes is known to be affected by Dex-stimulation in various cell types, that is, NFKBIA (Alcorn et al, 2004;Chauhan et al, 2002;Medh et al, 2003), TNFAIP3 (Galon et al, 2002), RGS2 (Homme et al, 2003), and VDUP (Medh et al, 2003). All selected genes were significantly induced (Student's t test; p < .01) upon Dex-stimulation ( Figure 2C) in the control samples.…”
Section: Gene Expression In Peripheral Blood Samplesmentioning
confidence: 95%
“…SP-A expression by HFL epithelial cells is stimulated by cAMP and IL-1, which enhance recruitment to the hSP-A promoter of the critical transcription factors, thyroid transcription factor 1 (TTF-1/Nkx2.1) and nuclear factor B (NF-B), and histone-modifying cofactors, which promote permissive changes in chromatin structure (5,6). By contrast, cAMP induction of hSP-A expression is inhibited by glucocorticoids (7)(8)(9) and TGF-␤ (10,11) and is blocked by hypoxia (6,12). Notably, TGF-␤ mediates inhibitory effects of hypoxia on lung alveolar development in neonatal mice (13) and down-regulates TTF-1 expression in lung adenocarcinoma cells (14).…”
mentioning
confidence: 99%